Failure to exploit learned spatial value information during visual search. Issue 7 (9th August 2018) - Won, Bo-Yeong; Leber, Andrew B.
ABSTRACT: In recent years there has been rapid proliferation of studies demonstrating how reward learning guides visual search. However, most of these studies have focused on feature-based reward, and there has been scant evidence supporting the learning of space-based reward. We raise the possibility that the visual search apparatus is impenetrable to spatial value contingencies, even when such contingencies are learned and represented online in a separate knowledge domain. In three experiments, we interleaved a visual choice task with a visual search task in which one display quadrant produced greater monetary rewards than the remaining quadrants. We found that participants consistently exploited this spatial value contingency during the choice task but not during the search task – even when these tasks were interleaved within the same trials and when rewards were contingent on response speed. These results suggest that the expression of spatial value information is task specific and that the visual search apparatus could be impenetrable to spatial reward information. Such findings are consistent with an evolutionary framework in which the search apparatus has little to gain from spatial value information in most real world situations.